The Potential of Domesticating Huntsman Spider (Spariolenus Aratta) and Its Nutritional Profile as Feed for Improved Food Security - Mwale, Tehillah (JOOUST, 2022)
Though not heavily researched, Spiders hold the possible key to new and innovative development by being a source of biological control and playing a role in food security. However, despite this potential, arachnids (spiders) have not been traditionally included informal science education as a feed source despite their abundance, familiarity, and ease of maintenance in captivity. This research sort of evaluating the effect of selected feed sources on the domestication of huntsman spiders, determining the nutritional profile of the spider, and assessing farmers' knowledge on the use of spiders as a source of feed for livestock. The spiders were reared for 14 weeks, with a total of 90 spiders under observation for six weeks, fed on feed sources: crickets, black soldier fly larva, and fruit flies. The experimental design was a completely randomized block design, replicated three times, with ten spiders per experimental unit. Nutritional analysis was done using Kjeldahl digestion tube, UV-VISIBLE spectrophotometer, flame photometer, and atomic absorption spectrophotometer. From the results of the three feed sources provided, the spiders fed on crickets showed a higher growth with means: 0.46 cm for leg span, 0.34cm for abdominal length, and 0.16 cm for abdominal width. Nutritional determination gave; crude protein = 77.35%, sodium = 122 mg/kg, calcium = 0.6 mg/kg, potassium =183 mg/kg, magnesium = 0.02 mg/kg, phosphorous = 2.07 mg/kg. Farmers are not aware of the use of spiders as a source of feed and regard them as poisonous to humans. However, farmers are willing to use them as a feed source for poultry. In conclusion, the huntsman spider can be domesticated best on crickets in terms of feed. They are rich in nutrient content and can serve as an alternative feed for livestock.